A response to Ralph F. Shangraw, jr. and Michael M. Crow: a critique of the design science approach to public administration - Overman, E. Sam (1998)
The design sciences are again making headway in public administration, public management, and public policy. The design science approach is a viable alternative to more traditional approaches, but it is also loaded with potentially negative implications and problems for the field. Two questions are posed here, one addressing the relationship of design science to systems theory, the other addressing the relationship of design science to political theory. I conclude that while it is a valuable exploration, design science must advance beyond its more naive theoretical assumptions and practical constraints if it is to become a legitimate contender in public administration theory debate. Advocating the rational design science approach for public administration in the normative context of the Minnowbrook forum is a tenuous position at best. - Reproduced
Keywords: Public administration